Majlis Perbandaran Hang Tuah Jaya smart apps (myMPHTJ) - Sallehudin, Noor Syarafina; Zulkifli, Zureen Natasya; Haron, Norhazlan; Teriman, Suharto; Mohd Zukifli, Muhamad Irham; Che Soberi, Mohamad Daniel Mustaqim; Johari, Ani Aznie (Universiti Teknologi MARA, Kedah, 2023)
Websites, and online applications have widely been used either in local authorities or private sector agencies. However, there are issues highlighted in the Malaysia Smart City Framework (2018) under the smart government tier, citing lack of public information sharing from the government, low quality in e-government services, and lack of information and data sharing in and between government agencies. The aim of this study is to propose an integrated application that is user friendly and highlights all the information that is needed by the public as well as tourists. This study adopts contentanalysis method to explore data attributes particularly on websites and online applications developed by the local authority of Majlis Perbandaran Hang Tuah Jaya (MPHTJ). Interview sessions were held with tourists and local people to identify the information they usually need to be included in the application. Findings revealed that there is plenty of information sought by local people and tourists such as information about tourism, land use, traffic, and transportation as well as infrastructure and utilities. Unfortunately, there is no integration between all the existing websites and applications. Hence, an application called myMPHTJ was proposed to integrate these websites and applications from the various departments within MPHTJ. The integration is expected to offer ease of use by the local people as well as tourists in MPHTJ. It is hoped that the development of this application would benefit not only Majlis Perbandaran Hang Tuah Jaya authority but also other local authorities as well.